The sterling area – parts II and III - WIGHTMAN, D. (PSL Quarterly Review, 2014)
The article examines the war and postwar vicissitudes of the sterling area, bringing to limelight features and questions of present and immediate significance for the current system of international payments as a whole. JEL: E42